Pengaruh Inklusi Keuangan, Pendapatan, dan Kontrol Diri Terhadap Perilaku Menabung Nasabah Bank Konvensional di DKI Jakarta - Mulya, Lena - (IAIN Kendari, 2024)
This study aims to determine Financial Inclusion, Income, and Self-Control on Saving Behavior of Conventional Bank Customers in DKI Jakarta. The method used in this study is the purposive sampling method where the customer sample is 163 respondents. Data processing and analysis techniques use descriptive statistical analysis, Convegent Validity, Discriminant Validity, Average Variance Extracted (AVE), Reliability Test, R-Square, F-Square Test, Path Coefficient, and Hypothesis Testing. The results of the study show that partially Financial Inclusion (X1) has no significant effect on Savings Behavior, while the variables Income (X2) and Self-Control (X3) have a positive and significant effect on Savings Behavior (Y).